The Physical Structure in Poem Entitled To Alison Cunningham, From Her Boy By Robert Louis Stevenson - Pawitra, Ilham (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
Poetry is one of a variety of literary works which built on a physical structure. Poetry relies on the use of concise language to express the poet’s feeling and thoughts, written in the most picturesque form. The physical structure in poetry consists of diction, figurative language, and imagery. This physical structure is used by the poet as a means to show the meaning contained therein. The purpose of this research is to examine and analyse the physical structure as a means for poets to express their feelings and thoughts. This research used a qualitative descriptive method with an expressive approach. This approach used is to analyse the meaning in depth through the physical form of poetry. The result shows the used of diction, figurative language, and imagery contained in poem entitled ‘To Alison Cunningham, From Her Boy’. Keywords: Poetry, Physical form, Robert Louis Stevenson